2013
DOI: 10.1097/jto.0b013e318276241c
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma: A Population-Based Study of the Management and Outcomes for the Province of British Columbia

Abstract: Survival rates in this population-based series were comparable to those in previously published reports. The ideal management of thymic tumors involves a multidisciplinary approach, particularly in locally advanced disease and selection of patients for adjuvant radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
1
17
2
1
Order By: Relevance
“…The recurrence rate of thymoma and thymic carcinomas varies according to different reports (Ruffini et al, 2014;Mizuno et al, 2015). Disease-free survival rates in our study were similar to previously published reports (Mariano et al, 2013;Luo et al, 2016). One interesting patient had metastatic thymoma disease at initial presentation and was treated with chemotherapy followed by radiotherapy and surgery.…”
Section: Discussionsupporting
confidence: 89%
“…The recurrence rate of thymoma and thymic carcinomas varies according to different reports (Ruffini et al, 2014;Mizuno et al, 2015). Disease-free survival rates in our study were similar to previously published reports (Mariano et al, 2013;Luo et al, 2016). One interesting patient had metastatic thymoma disease at initial presentation and was treated with chemotherapy followed by radiotherapy and surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, cases that were diagnosed as thymic carcinoma by any reviewer were excluded because thymic carcinomas have consistently been shown to be a distinct group of tumors that have a worse outcome than thymomas. 17,21,23,24 Our agreement rate of 62.0% for WHO classification of thymomas is higher than some of the previously reported rates, likely because our study includes only three reviewers and all reviewers have expertise in thoracic pathology and work together in one department. In contrast to our study, Zucali et al 7 reported a 49% agreement among four reviewers, at least one of which was a surgical pathologist without a specific interest in thymic malignancies.…”
Section: Discussioncontrasting
confidence: 52%
“…However, other investigators did not find age to be an important prognostic factor in thymoma. 7,14,15 Size of the tumor is a controversial prognostic factor in thymoma. Blumberg and colleagues 14 found that patients with tumors >11 cm had a worse prognosis, and Wright and colleagues 7 found that patients with tumors >8 cm had a worse prognosis than patients with smaller tumors.…”
Section: Discussionmentioning
confidence: 99%